Intravenous injection of adult human bone marrow mesenchymal stromal cells attenuates spinal cord ischemia/reperfusion injury in a murine aortic arch crossclamping modelCentral MessagePerspective - Hidekazu Nakai, MD; Yasuyuki Fujita, MD, PhD; Satoru Masuda, MT; Miki Komatsu, MT; Ayumi Tani, MT; Yutaka Okita, MD, PhD; Kenji Okada, MD, PhD; Atsuhiko Kawamoto, MD, PhD (JTCVS Open, 2021)
Objective: We sought to investigate the efficacy of human bone marrow mesenchymal stem/stromal cell (hBM-MSC) in a murine spinal cord ischemia/reperfusion (SCIR) model. Methods: C57BL/6J mice were subjected to SCIR by crossclamping the aortic arch and left subclavian artery for 5.5 minutes. Two hours after reperfusion, hBM-MSCs (hBM-MSC group) or phosphate-buffered saline (control group) were intravenously injected without immunosuppressant. Hindlimb motor function was assessed until day 28 after reperfusion using the Basso Mouse Scale (BMS). The lumbar spinal cord was harvested at hour 24 and day 28, and the histologic number of NeuN-positive motor neurons in 3 cross-sections of each lumbar spinal cord and the gene expression were evaluated. Results: BMS score was 0 throughout the study period in all control mice. BMS score was significantly greater in the hBM-MSC group than the control group from hour 8 (P < .05) to day 28 (P < .01). The numbers of motor neurons at hour 24 (P < .01) and day 28 (P < .05) were significantly preserved in the hBM-MSC group than the control group. mRNA expression levels of proinflammatory cytokines were significantly lower (P < .05), and those of insulin-like growth factor-1 (P < .01) and proangiogenic factors (P < .05) were significantly greater in the hBM-MSC group than the control group at hour 24. Conclusions: hBM-MSC therapy may attenuate SCIR injury by preserving motor neurons, at least in part, through inhibition of proinflammatory cytokines and upregulation of proangiogenic factors in the reperfusion-injured spinal cord.